The role of energy prices in the Great Recession: A two-sector model with unfiltered data - Nasir Aminu; David Meenagh; Patrick Minford (Cardiff University, Cardiff Business School, 2018)
We investigate the role of energy shocks during the Great Recession. We study the behaviour of the UK energy and non-energy intensive sectors firms in a real business cycle (RBC) model using unfiltered data. The model is econometrically estimated and tested by indirect inference. Output contraction during the Great Recession was largely caused by energy price and sector-specific productivity shocks, all of which are non-stationary and hence tend to dominate the sample variance decomposition. We also found that the channel by which the energy price shock reduces output in the model is via the terms of trade: these fall permanently when world energy prices increase and as substitutes for energy inputs are strictly limited there are few reactions via production channels. Therefore, there is no other way to balance the deteriorating current account than through lower domestic absorption.
Keywords: 330